Role of the Head School in Management of Foundation Funds in Increase Quality learning at MtsN 5 Cirebon - H. Soro , Suharyanto; Azmalia, Faiz Ramdhan; Hidayatullah, Raihan Nur (Civiliza Publishing, Indonesia., 2025)
Study This aim For find and analyze role head school in management of Foundation funds in increase quality learning at MtsN 5 Cirebon. Using approach studies case with paradigm qualitative research​ This involving informant key consisting of from head school, deputy principal school, treasurer schools, senior teachers, and representatives committee school. Research results show that head school own a very comprehensive role in management of foundation funds, including function as planners, implementers, managers and evaluators in all over cycle management finance. Policy foundation that allocates 30% of the total budget For sector education supported by the system supervision involving foundation organs and mechanisms​ strict reporting​ For ensure accountability and transparency . Impact foundation fund management to Quality very significant learning, shown through style leadership head transparent, accountable, effective and efficient schools. The programs implemented succeed increase quality learning, reducing burden financing parents, and preventing student separated school. Response positive student towards the improvement program quality and increase facility comprehensive education​ show effectiveness foundation fund management in reach objective improvement Quality learning. Research conclusions This contribute theoretical and practical in development management financing education in madrasas, especially in optimization impactful management of foundation funds positive to improvement Quality learning in a way sustainable.